The therapeutic alliance as a component of risk management and assessment in forensic mental health - Swart Barbour, Tania (Department of Psychiatry and Mental Health, 2018)
Background: Few forensic mental health facilities in South Africa use formal risk assessment instruments to monitor risk and recovery of forensic state patients. The study set out to examine the usefulness of the therapeutic alliance as a proxy measure of violent recidivism in a forensic state facility. The study proposed that the nature and strength of the therapeutic alliance is associated with risk of violence in a forensic population and that attachment security is a relevant factor in this relationship. Additional related factors were studied including demographic and contextual data and their influence on the alliance and risk. Design and method: A quantitative research method was used to sample both inpatients and outpatients (n=131) using a naturalistic, cross-sectional research design. Statistical analyses focussed on regression modelling and addressed mainly the statistical associations between ratings of the different variables. Various psychometric tests were administered and scored and entered into a database. It was hypothesised that a strong (positive) therapeutic relationship measured with the Dual- role Relationship Inventory-Revised (DRI-R) questionnaire is associated with low risk for violence using the Historical, Clinical, Risk Management (HCR-20) scale. Findings: Essentially there was a direct association between the therapeutic alliance and violent recidivism, that is, men with a strong therapeutic alliance have lower risk for violent behaviour. Key practitioner type was considered to be highly influential in establishing positive alliances and as a mediator of potential violent recidivism. An insecure attachment style was dominant in the study sample and insecure states of mind partially influenced current therapeutic alliances with an associated increased vulnerability for violence. Positive psychotic symptoms remained a high-risk factor for violence and criminal histories and antisocial behaviour may continue to present a risk for recidivism in the absence of psychosis. Conclusion: Violent recidivism can be adequately monitored by the DRI-R. Affiliation and control are not mutually exclusive in forensic mental health care. Addressing attachment deficits prevalent in this population may be useful in informing both risk and recovery. Symptom reduction remains an important aim in treatment and risk management. Ratings of the alliance by practitioners and how it concurs with risk is an area for further research. Key words: Therapeutic alliance, dual-role relationship, risk assessment, violence, attachment, state patients, recovery